Fluorene-Modified Zinc Porphyrin as Low-Cost Hole-Transporting Material for Efficient Perovskite Solar Cells - Wang, Yu-Duan; Shao, Jiang-Yang; Lan, Zhong-Rui; Zhong, Yu-Wu (Organic Materials, 2022)
Abstract The potential of porphyrin derivatives as hole-transporting materials (HTMs) for perovskite solar cells (PSCs) has been demonstrated. The structural engineering of porphyrin HTMs provides an important means for further improvement of the performance of PSCs. Herein, a zinc-porphyrin derivative (ZnP-FL) decorated with four fluorene-terminated triarylamines is presented. The lab synthesis cost of ZnP-FL is estimated to be around $32.2/g. It exhibits good charge-transport ability and thermal stability. A high power conversion efficiency (PCE) of 19.31% is achieved by using ZnP-FL HTM ( V oc = 1.08 V; J sc = 24.08 mA · cm −2 ), which is distinctly higher than that of a control HTM without the fluorene groups (PCE = 17.75%; V oc = 0.97 V; J sc = 24.04 mA · cm −2 ). This performance enhancement is mainly attributed to the improved open-circuit voltage, which benefits from the stabilized HOMO level of ZnP-FL. In addition, the porphyrin HTM-based PSCs show superior air and thermal stability to the device with the standard HTM spiro-OMeTAD. These results demonstrate that the low-cost and easily accessible porphyrin derivatives are promising HTMs for efficient and stable PSCs.